Vitamin D and Reduced Academic Stress of Health Students - Kusmiyati, Yuni; Suryani, Emy; Herawati, Lucky; Firdausi, Amalia (Kesmas, 2020)
Stress conditions can reduce academic ability, influencing student grade point averages and encouraging negative behaviors. The object of this research was to discern the influence of vitamin D in the reduction of academic stress of health students. The study used a randomized controlled trial (RCT). The population was midwifery students who lived in the Health Polytechnic dormitory, Ministry of Health, Yogyakarta, in 2017. Samples were 77 students of midwifery who did not suffer from any chronic disease, nor did they experience academic stress. They all agreed to become research subjects. Samples were 39 respondents in a treatment group who were administered 1 tablet of 400 mg of vitamin D supplement daily, for 30 days. A control group was given a placebo. Academic stress was assessed by means of the Depression, Anxiety, and Stress Scale 42 (DASS 42). Data were analyzed by using linear regression. The results showed that daily vitamin D supplement reduced academic stress (p-value 0.000 < 0.05). One dose of 400 international units (IU) of vitamin D daily for 30 days could reduce academic stress by 11.28 points. To reduce academic stress, students should consume vitamin D and expose their skin to sun rays with ultraviolet.